Design of motion, skill tests as a part bateery For testing football young players - Shafy, Saleh; Ali, Ayed (Journal of Physical Education, 2014)
Tests ara an important tool for evaluation. using tests has its own rules to function the results of these tests and rules to be based on them. constructing battries for different athletic games gain more attention. football is a droup game where many skills and abilities interfere.it is important that constructing a battery require some cases more closel to real playing. factor analysis is the suitable way for constructing the battery. The study aims at: 1- Desigining some skill tests of football 3- Finding factor truth for designed skill tests 4- Constructing a battery for choosing basic skill of football 5- Establishing the criteria for the skill battery of football The descriptive approach is used by utilizing correlative style. the study population consist of 269 of football players chosen deliberately and they cosseted of the study population. The researcher has used various tools to reach the data. these tools include the scientific survey of the references, interviews, questionnaire, determining the basic skill, choosing the tests of basic skills in addition to designing some modern tests. after collecting the questionnaire from,16skill tests were chosen. then some explorative tests were done in order to identify the baic skills of tests.the results of these experiments show that four of them failed.so the skill tests for factor analysis are(16)skills tests,(14)designed skill tests, and (14)skill pretests in football. these tests were applied on the study sample.the following statistical means were used by the researcher:mean, standarddeviation, percentage, simple coefficient correlate, and factor analysis.